Recurrent spinal primitive neuroectodermal tumor with brain and bone metastases: A case report. Issue 46 (November 2017) - Chen, Frank; Chiou, Shyh-Shin; Lin, Sheng-Fung; Lieu, Ann-Shung; Chen, Yi-Ting; Huang, Chih-Jen
Abstract: Rationale: Primary spinal primitive neuroectodermal tumor (PNET) is relatively rare in all age groups, and the prognosis in most cases of spinal PNETs appears to be poor, with a median patient survival of 1 to 2 years. We present a case with recurrent spinal PNET with brain and bone metastases that was successfully treated by multimodality treatment. Patient concerns: A 14-year-old teenage girl had suffered from progressive left upper back pain with bilateral lower legs weakness and numbness for 1 year. After treatment, left neck mass was noted 3 years later. Diagnoses: Initially, magnetic resonance imaging (MRI) showed neurogenic tumor involving intradural extramedullary space of T5-T10. Pathology report showed PNET (World Health Organization grade IV) featuring lobules of neoplastic cells with round regular nuclei, high nucleus-to-cytoplasm ratio, and fibrillary cytoplasm. At the time of tumor recurrence, chest MRI then showed recurrent tumor at T2-T3 level of the epidural space with right neural foramina invasion. Brain MRI showed extensive bilateral calvarial metastases and leptomeningeal metastases in the right frontoparietal regions. Bone scan showed multiple bone metastases. Interventions: T-spine tumor removal and adjuvant radiotherapy (RT) to T-spine tumor bed were performed in the initial treatment. After clinical tumor recurrence, tumor removal was done again. She then received chemotherapy followed by whole brain irradiation with hippocampal sparing with 35 gray in 20 fractions. Outcomes: After treatment, follow-up images showed that the disease was under control. There was no neurological sequela. She has survived more than 7 years from diagnosis and more than 4 years from recurrence to date. Lessons: Multimodality treatments including operation, RT, and chemotherapy should be considered in the initial treatment planning, and salvage chemotherapy was useful in this case.